Analisis Habituasi Shalat Dzuhur Berjama’ah Di Smp Ma’arif Kalibawang Wonosobo Tahun 2023/2024 - Erniatun Fuadah; Sri Haryanto; Muhtar Sofwan Hidayat (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Habituation is a process in which the response to a particular stimulus decreases with repeated exposure to that stimulus. In the context of psychology, habituation often refers to a decrease in response to a harmless or unimportant stimulus after repeated exposure, which can result in changes in an individual's behavior. This process is a form of non-associative learning in which individuals become accustomed to the same stimuli and their response to these stimuli decreases over time. The congregational midday prayer is the performance of midday prayers together by a group of individuals which is performed in a place of worship, such as a mosque, prayer room, or a designated area at a school or other place. In congregational prayer, an imam leads the prayer, while the congregation or people present follow the imam in carrying out the prayer movements and reciting verses from the Koran and prescribed prayers. This research aims to find out how the habituation or habituation of midday prayers in congregation is carried out and what the impact of habituation is to midday prayers in congregation, as well as what are the inhibiting and connecting factors for the habituation of midday prayers in congregation at Ma'arif Kalibwang Middle School, Wonosobo. This research uses a type of qualitative research using a descriptive approach. Qualitative research is research that uses observation, interviews, content analysis and data collection methods. The location of this research is Ma'arif Kalibawang Middle School, Wonosobo. After the data is collected, it is then analyzed using data analysis, namely, data reduction, data presentation and conclusions. The results of this research show the activities of getting used to midday prayers in congregation at Ma'arif Kalibawang Middle School, Wonosobo. First, the activity of getting used to midday prayers in congregation at Ma'arif Kalibawang Middle School, Wonosobo has gone well. Second, the impacts obtained include students being able to increase awareness of praying, students instilling discipline, and students being able to increase their devotion to prayer. Third, the inhibiting and supporting factors in the implementation of congregational midday prayers include: 1) Inhibiting factors include students' lack of awareness in worship and inadequate facilities. 2) Supporting factors include student awareness and motivation from teachers, complete facilities and infrastructure, and parents and the community around the school who support and motivate the activities of carrying out midday prayers in congregation.